Orbital teratoma in the foetus: a rare case without proptosis - Chen, Xi (BMC Ophthalmol, 2020)
BACKGROUND: Congenital orbital teratoma is relatively rare, and few reports of prenatal ultrasound findings in such cases have been published. CASE PRESENTATION: A rare case of congenital orbital teratoma at 24 + 2 weeks of gestation was previously diagnosed as microphthalmia, noting how orbital teratoma without proptosis is different from microphthalmia, retinoblastoma and intracranial teratoma. Ultrasound examination, analysis of gross specimens, and histopathological evaluation confirmed the diagnosis of orbital teratoma. CONCLUSION: Prenatal ultrasound examination is useful for diagnosis and differential diagnosis of congenital orbital teratoma.